(NrASSKAZY (B/s - (NgORXKIJ(B, (NmAKSIMs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B,s, 1981)
(Nw KNIGU WYDA@]EGOSQ SOWETSKOGO PISATELQ m(B. (NgORXKOGO (B(1868$1 (B1936) (NWO[LI RASSKAZY (B1892 $1 (B1898 (NGODOW(B: (S0(NmAKAR ~UDRA(S1(B, (S0(NsTARUHA iZERGILX(S1(B, (S0(N~ELKA[(S1 (NI DR(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs